Multilevel converter with fault-tolerant capability for the switched reluctance machine - Fernão Pires, V. (2021)
Many critical systems require permanent operation even in a situation of a fault. In this way, electrical drives that are associated to these systems must have fault-tolerant capability. One of the machines that are used in many systems is the switched reluctance machine (SRM). To achieve the best performance with a wide speed range, multilevel converters are one of the adopted options. Thus, this paper presents a new multilevel converter for the SRM with fault-tolerant capability. The proposed solution allows to maintain the drive at operation for both conditions of opencircuit and short-circuit power semiconductor fault. Their operation in normal and fault-tolerant modes for the 8/SRM is presented in detail. To verify the capability and operation modes of the proposed system several simulation tests will be presented.